1967
DOI: 10.1515/agph.1967.49.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Aristoteles, der Lehrer. Alexanders von Aphrodisias

Abstract: Aristoteles, der Lehrer. Alexanders von Aphrodisias von PAUL MORAUX (Berlin) ber die philosophische Ausbildung Alexanders von Aphrodisias sind wir ebenso schlecht informiert wie ber die sonstigen Umst nde seines Lebens. Unter den zweifellos zahlreichen Sch lern und Bewunderern des ber hmtesten aller griechischen Interpreten des Aristoteles fand sich leider keiner, der wie etwa Poiphyrios f r Plotin die wichtigsten Lebensdaten des Meisters in einem ios piet tsvoll aufzeichnete. Das wenige, was wir von seinem Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The text is problematic, and Moraux suggested that Elias' source must have read ὁ διδάσκαλος Ἀλεξάνδρου instead of ὁ διδάσκαλος Ἀλέξανδρος. See Moraux 1967, Accattino 1985. Cf.…”
Section: Logic and Ontologymentioning
confidence: 99%
See 1 more Smart Citation
“…The text is problematic, and Moraux suggested that Elias' source must have read ὁ διδάσκαλος Ἀλεξάνδρου instead of ὁ διδάσκαλος Ἀλέξανδρος. See Moraux 1967, Accattino 1985. Cf.…”
Section: Logic and Ontologymentioning
confidence: 99%
“…Cf. Moraux 1942 Galen, On Habits 11.4-12 Müller (= Sharples 2010a, IZ), Moraux 1967. In the treatise written during the rule of Marcus Aurelius, Galen describes as a recent event this philosopher's illness and death, so we would have the terminus post quem non as AD 180.…”
Section: Logic and Ontologymentioning
confidence: 99%